NATTICE, de la naturaleza al diseño - Martínez García, Nayeli (Universidad Michoacana de San Nicolás de Hidalgo, 2020)
Throughout history, man has always tried to improve his life span in this world, very often using design as a means to achieve this goal, for this reason, many architects make an effort to investigate and experiment with new forms, materials or structures. In this project, a series of explorations and experiments were carried out using processes based on biomimetics as the main element of inspiration from nature. The application of geometrization as a tool for the various proposals was successfully carried out, managing to cover the characteristics required for its application and experimentation. The use of parametric design has managed to establish itself as an innovative and enriching experience of the architectural project. And in conjunction with living architecture and experimentation, it can open a large number of doors to new biological, digital and / or sustainable techniques.

A lo largo de la historia el hombre siempre ha intentado mejorar su estancia de vida en este mundo, muy a menudo sirviéndose del diseño como medio para alcanzar dicho objetivo, por ello, muchos arquitectos nos esforzamos en investigar y experimentar formas, materiales o estructuras nuevas. En este proyecto, se realizó una serie de exploraciones y experimentos a partir de procesos basados en la biomimética como principal elemento de inspiración de la naturaleza. Se llevó a cabo con éxito la aplicación de la geometrización como herramienta para las diversas propuestas, logrando cubrir las características requeridas para su aplicación y experimentación. La utilización del diseño paramétrico, ha conseguido establecerse como una experiencia innovadora y enriquecedora del proyecto arquitectónico. Y en conjunto con la arquitectura viva y la experimentación puede abrirnos una gran cantidad de puertas hacia novedosas técnicas biológicas, digitales y/o sostenibles.
Facultad de Arquitectura. Maestría en diseño avanzado
Keywords: info:eu-repo/classification/cti/4; FA-M-2020-1313; Biomimésis; Arquitectura viva; Celosías naturales; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2606